Application of Oilfield Casing Cathodic Protection Technology - LIU Li, LIU Jie, ZHANG Yong - qiang, YANG Zhi - gang, LV Shuo, TA Chuan, HUANG Guo - sheng (Cailiao Baohu)
Casing corrosion is a common problem in oil and gas production. Generally, the casing is buried deep in the ground, and the underground environment is more complicated. Cathodic protection technology can protect the casing and extend the service life of the casing. In this paper a complete cathodic protection construction method was presented through a complete set of cathodic protection system technical design. The influence of different anodes buried depth on the potential distribution of cathodic protection was calculated by using the numerical simulation technology of Beasy software, and the protection effect of impressed current cathodic protection on the bottom hole was evaluated. The simulation results showed that the cathode protection scheme of well group could be protected with the anode installed in the middle of the well group, the horizontal distance from the well group of 12 m, and the buried depth of 100 m. The test results showed that this technology had obvious anti - corrosion effects, and the casing corrosion phenomenon was been improved significantly, which could meet the anti - corrosion needs under different conditions, indicating that further popularization tests could be carried out in oil fields.